Post‐Transplant Lymphoproliferative Disorder in Kidney Transplant Recipients: A Single‐Center Experience in Japan. Issue 2 (7th March 2016) - Ishihara, Hiroki; Shimizu, Tomokazu; Unagami, Kohei; Hirai, Toshihito; Toki, Daisuke; Omoto, Kazuya; Okumi, Masayoshi; Imai, Yoichi; Ishida, Hideki; Tanabe, Kazunari
Abstract: Post‐transplant lymphoproliferative disorder is a serious complication of solid organ transplantation; however, few large studies have been performed in Asian institutions. We review our single‐center experience with post‐transplant lymphoproliferative disorder patients in Japan. We retrospectively evaluated patients with post‐transplant lymphoproliferative disorder following kidney transplantation between January 1985 and December 2013. The patients were divided into early‐onset post‐transplant lymphoproliferative disorder (<1 year) and late‐onset post‐transplant lymphoproliferative disorder (≥1 year) groups. Thirteen patients had the disorder, an incidence rate of 0.75% (13/1730). Early‐onset post‐transplant lymphoproliferative disorder ( N =  3) had not occurred for the last two decades. In the late‐onset group ( N =  10), the median time of onset was 108.7 months. The Kaplan–Meier 10‐year overall survival rates were 76.9% and 95.4% in patients with and without the disorder, respectively ( P  = 0.0001). Post‐transplant lymphoproliferative disorder significantly affected transplant recipients' mortality. Late‐onset occurred even > 10 years after transplantation; therefore, long‐term monitoring of patients is needed.